Analytical Approaches on the Attractivity of Solutions for Multiterm Fractional Functional Evolution Equations. (21st June 2022) - Li, Xiangling; Niazi, Azmat Ullah Khan; Hafeez, Farva; George, Reny; Hussain, Azhar
Abstract : The most important objective of the current research is to establish some theoretical existence and attractivity results of solutions for a novel nonlinear fractional functional evolution equations (FFEE) of Caputo type. In this respect, we use a familiar Schauder's fixed-point theorem (SFPT) related to the method of measure of noncompactness (MNC). Furthermore, we consider the operator E and show that it is invariant and continuous. Moreover, we provide an application to show the capability of the achieved results.